Environmental and health impacts (particulate matter and noise) of airport infrastructure upgrading: Kuala Lumpur International Airport 2 - Sahrir, Syazwani; Bachok, Syahriah; Mohamed Osman, Mariana (Elsevier, 2014)
The paper studies the environmental impacts of airport expansion of Kuala Lumpur International Airport 2 (KLIA2). Some of significant environmental concerns in airports growth are noise and air quality. Several airborne particulate matter samplers and sound level meter used to record both noise and particulate matter levels. The findings suggested that increased of construction and land use intake had significant relations with the noise and particulate matter (PM) levels. The PM levels at the surrounding living area are above the recommended levels. The findings of the study hoped to assist in providing a better insight into the intangible costs and benefits derived from an airport expansion.